The Effectiveness of Guided Inquiry-Based Worksheet on Synthetic and Natural Food Colorant Thin Layer Chromatography Practicum in Developing Scientific Explanation Skills - Nuraini, Valen Dwike Sabila; Helsy, Imelda; Nurhayati, Nurhayati; Aisyah, Riri; Sukmawardani, Yulia (Jurnal Pijar Mipa, 2025)
Scientific explanation is an essential skill in chemistry learning because it connects scientific principles and objective evidence. This study aims to describe the application of guided inquiry-based learning in thin-layer chromatography experiments of synthetic and natural food coloring to develop students' scientific explanations in learning applications. This study used a pre-experimental method with a post-test only one-shot case study design. In the implementation of learning, the implementation rate reached 87%. The average scores for worksheets and scientific explanation tests were 78 and 79, respectively. This indicates that the application of guided inquiry-based worksheets through TLC experiments is practical in developing students' scientific explanation skills. This experiment can be adopted in broader chemistry learning contexts by integrating guided inquiry with thin-layer chromatography using real food colorants, thereby fostering scientific thinking and providing students with hands-on experience that emphasizes the relevance of chemistry in everyday life.